AN ANALYSIS OF STUDENTS’NEEDS IN LEARNING ENGLISH AT HIGHER EDUCATION OF INFORMATICS - . Marjito (STMIK Mardira Indonesia, Bandung, 2015)
The need for proficiency in the English language in college students is very important for improving the competence in the teaching and learning process as well as a provision in the face of the world of work upon graduation. To achieve effectiveness and alignment between the needs of the student’s ability hence the need for research on the needs of the students in learning English in higher education, especially college students informatics. Keywords: Student Needs, English Learning Abstrak Kebutuhan akan kemampuan dalam berbahasa inggris pada mahasiswa perguruan tinggi sangat penting untuk peningkatan kompetensi mahasiswa dalam melakukan proses belajar mengajar maupun sebagai bekal dalam menghadapi dunia kerja pada saat lulus kuliah. Untuk mencapai efektifitas dan keselarasan antara kebutuhan dengan kemampuan mahasiswa maka perlu adanya penelitian mengenai kebutuhan mahasiswa dalam belajar bahasa inggris di perguruan tinggi khususnya mahasiswa perguruan tinggi informatika. Kata Kunci: Kebutuhan Mahasiswa, English Learning